The exterior squares of some crystallographic groups - Mat Hassim Hazzirah Izzati, Sarmin Nor Haniza, Mohd Ali Nor Muhainiah, Masri Rohaidah, Mohd Idrus Norashiqin, (N/A, 2013)
The exterior squares of some crystallographic groups by Mat Hassim Hazzirah Izzati, Sarmin Nor Haniza, Mohd Ali Nor Muhainiah, Masri Rohaidah, Mohd Idrus Norashiqin,